Feasibility Study of Park and Ride City of Depok - Khodam Fauzi, Muhamad; Murtedjo, Tedy; Rulhendri, Rulhendri (Universitas Ibn Khaldun Bogor, 2022)
Depok City is a city in West Java Province, Indonesia. The city is located just south of Jakarta, which is between Jakarta and Bogor. The total population of Tangerang Regency in 2020 is ± 2,457,745 people according to the Central Statistics Agency (BPS) of Depok City. Depok City which has an area of 200.29 km. This research was conducted to determine the feasibility level of the Park and Ride development plan in Depok City. Traffic counting surveys and interviews were carried out on the main road sections which were then processed using Microsoft Excel to determine the parking accumulation until the fluctuation of motorbikes and cars was known. Furthermore, the interview data is processed to determine the amount of public interest in the development of Park and Ride which is reviewed based on gender, age, trip duration, trip intent, parking duration, monthly fuel expenditures, desired parking rates and those who agree to use Park and Ride when the survey was conducted. at 06.00-21.00 WIB on Jalan Jatijajar Terminal area. From the results of processing this data using Microsoft Excel, the characteristics of Park and Ride facilities users and also the number of users of Park and Ride facilities for motorbikes were found to be 421, while for cars of 116 with a plan age until 2021, this proves that there is a need to increase interest in motorbikes. Park and Ride development at Jatijajar Depok Terminal.